2018
DOI: 10.3390/nano8060400
|View full text |Cite
|
Sign up to set email alerts
|

Diazotization-Coupling Reaction-Based Determination of Tyrosine in Urine Using Ag Nanocubes by Surface-Enhanced Raman Spectroscopy

Abstract: A novel, simple, and highly sensitive method was developed to detect the concentration of tyrosine-derived azo dye indirectly using silver nanocubes (AgNCs) as a substrate on a super-hydrophobic silver film by surface-enhanced Raman spectroscopy (SERS). Diazotization-coupling reaction occurred between diazonium ions and the phenolic tyrosine, resulting in three new typical peaks in the SERS spectrum of the azo dye that was formed on the AgNCs, indicating strong SERS activity. Subsequently, the limit of detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…In addition, we observe identical crossover behavior between the protonated and deprotonated forms of the carboxyl residue of tyrosine. The COO − is usually the origin of the electrostatic adsorption of tyrosine and several amino acids on metallic surfaces and is thus not clearly discernible in SERS . In contrast, we observed that the increase in the intensity of COO − stretch (1,640 cm −1 ) is also closely associated with the concomitant decrease in the intensity of C―O stretch (1,240 cm −1 ; Figure b), both these processes occurring with increase in pH.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, we observe identical crossover behavior between the protonated and deprotonated forms of the carboxyl residue of tyrosine. The COO − is usually the origin of the electrostatic adsorption of tyrosine and several amino acids on metallic surfaces and is thus not clearly discernible in SERS . In contrast, we observed that the increase in the intensity of COO − stretch (1,640 cm −1 ) is also closely associated with the concomitant decrease in the intensity of C―O stretch (1,240 cm −1 ; Figure b), both these processes occurring with increase in pH.…”
Section: Resultsmentioning
confidence: 59%
“…This poses serious problems for SERS substrates that are fabricated through bottom‐up approaches that heavily rely on precise control over pH and temperature . For instance, spectral shift accompanied by intensity fluctuation is observed while employing SERS to detect amino acids such as tyrosine with Ag sols . The spectral shifts in these cases predominantly originate from charge‐transfer interaction between analyte and SERS substrate and are thus not necessarily exclusively dependent on the charge of the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) was first reported by Hendra, Fleischmann, and McQuillan [1], who studied the adsorption of pyridine onto roughened silver. The technique has since been widely used in biological [2], medical [3,4], environmental engineering [5], materials science [6,7], and quality analysis applications [8] because it offers increased Raman intensity by several orders of magnitude. Further, it offers sufficient sensitivity for single-molecule detection [9] and trace chemical analysis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the coffee ring effect results in the majority of dispersed or dissolved nanoparticles and chemicals being dragged to the edge of the droplet mainly due to the capillary flow, leading to the difficulty to obtain reproducible SERS spectrum for the analyte (Culha, ; Zhu et al., ). Quite some efforts have been made to suppress the coffee ring effect through control the capillary flow so that more even distribution of nanoparticles and analyte molecules onto a sample holder could be obtained (Culha, ; Lu et al., ; Zhu et al., ). However, most recently, there are reports on applying coffee ring effect to separate and concentrate analyte molecules and nanoparticles from the bulk solution to improve the performance of SERS analysis (Mampallil & Eral, ; Pan et al., ; Xu, Du, Jing, Zhang, & Cui, ).…”
Section: Sers For Trace Analysis Of Organic Chemicals In Foodsmentioning
confidence: 99%